Determination of glass transition temperature of a polyarylate by using both inverse gas chromatography and electrical conductivity measurements - Serin, M; Sakar, D; Cankurtaran, O; Yilmaz, FK (NATL INST OPTOELECTRONICS, 2004)
The glass transition temperature of a polyarylate was found from the slope changes of the logarithms of specific retention volume as well as electrical conductivity with reciprocal absolute temperature plots. The glass transition of the copolyester of bisphenol-A with terephthalic acid and isophthalic acid (50/50) Ardel(R)D-100 was determined as 463 K on the retention diagram for n-butyl acetate and n-octane obtained between 393 and 513 K by inverse gas chromatography. Electrical characterization was realized on the base of dc conductivity-temperature measurements for the films having three different thicknesses being 10.00, 5.00 and 2.50mum. The measurements were carried out in vacuum and dark. The electrical conductivity of the polymer was measured in Al/polymer/Al structure over the temperature range of 300 - 520 K. The activation energies of the samples were determined depending on the sample thickness. The glass transition temperature of Ardel(R)D-100 were found as 466 K with an average value of three film samples from conductivity measurements.
Keywords: ARDEL; glass transition temperature; inverse gas chromatography; electrical characterization; dark conductivity; POLY PHENYL SULFONE; Materials Science; Optics; Physics